Mitologi Perkawinan Ngalor-Ngulon Masyarakat Muslim Desa Mlilir Kecamatan Berbek Kabupaten Nganjuk: Perspektif Teori Fungsionalme Struktural - Zayad Abd. Rahman; Ulin Na’mah; Ahmad Sulton Ariwibowo (LP2M Institut Agama Islam Negeri (IAIN) Kediri, 2020)
One of the social phenomena that occurs in Indonesia is the prohibition of traditional Javanese marriages from ngalor-ngulon. Ngalor-ngulon marriage is a prohibition for the people in Mlilir Village to conduct marriages in the direction of the groom's house to the bride ngalor-ngulon, meaning that a man is not allowed to marry a woman whose house is north to west and vice versa. This tradition is unique and full of meaning, especially in terms of people's beliefs about the law, which according to researchers is called newmena. Because of this uniqueness, this study aims to determine the factors that influence community beliefs and views of the people of Mlilir Village on the prohibition of Javanese traditional marriages in Muslim communities from the Perspective of Talcott Parsons' Structural Functionalism Theory. This research is a field research, namely research with data collection carried out from field activities. Data was collected by observing for one month and interviews with twelve respondents in written and oral form. The results of the study revealed that the factors that caused the community to maintain the prohibition of ngalor-ngulon marriage in Mlilir Village were the hereditary community beliefs, the majority of the people of Mlilir Village rarely opposed it, because this prohibition had been carried out long ago and is still being carried out until now. Analysis of the structural functionalism theory of the prohibition of marriage ngalor-ngulon Javanese custom In Muslim society, in reality the values, cultural norms, ideas or legal rules that apply are not fully able to answer the social needs of the community. So that individuals in the system must try to manage and overcome them with various alternatives to connect and adapt one part to another.